Bone Strength and Structural Deficits in Children and Adolescents With a Distal Forearm Fracture Resulting From Mild Trauma. (March 2014) - Farr, Joshua N; Amin, Shreyasee; Melton, L Joseph; Kirmani, Salman; McCready, Louise K; Atkinson, Elizabeth J; Müller, Ralph; Khosla, Sundeep
ABSTRACT Although distal forearm fractures (DFFs) are common during childhood and adolescence, it is unclear whether they reflect underlying skeletal deficits or are simply a consequence of the usual physical activities, and associated trauma, during growth. Therefore, we examined whether a recent DFF, resulting from mild or moderate trauma, is related to deficits in bone strength and cortical and trabecular bone macro‐ and microstructure compared with nonfracture controls. High‐resolution peripheral quantitative computed tomography was used to assess micro‐finite element‐derived bone strength (ie, failure load) and to measure cortical and trabecular bone parameters at the distal radius and tibia in 115 boys and girls with a recent (<1 year) DFF and 108 nonfracture controls aged 8 to 15 years. Trauma levels (mild versus moderate) were assigned based on a validated classification scheme. Compared with sex‐matched controls, boys and girls with a mild‐trauma DFF (eg, fall from standing height) showed significant deficits at the distal radius in failure load (–13% and –11%, respectively; p < 0.05) and had higher ("worse") fall load‐to‐strength ratios (both +10%; p < 0.05 for boys and p = 0.06 for girls). In addition, boys and girls with a mild‐trauma DFF had significant reductions in cortical area (–26% and –23%, respectively; p < 0.01) and cortical thickness (–14% and –13%, respectively; p < 0.01) compared with controls. The skeletal deficits in the mild‐trauma DFF patients were generalized, as similar changes were present at the distal tibia. By contrast, both boys and girls with a moderate‐trauma DFF (eg, fall from a bicycle) had virtually identical values for all of the measured bone parameters compared with controls. In conclusion, DFFs during growth have two distinct etiologies: those owing to underlying skeletal deficits leading to fractures with mild trauma versus those owing to more significant trauma in the setting of normal bone strength. © 2014 American Society for Bone and Mineral Research.